The associations of SEA-α thalassemia 1, XmnI-Gγ polymorphism and β-globin gene mutations with the clinical severity of β-thalassemia syndrome in Northern Thailand - Thanusak Tatu (2018)
At least three genetic factors including β-thalassemia mutations, α-thalassemia, and XmnI-Gγ polymorphism were shown to modify clinical symptoms in β-thalassemia disease. Objective: To determine associations of β-thalassemia mutations, SEA-α thalassemia 1, and XmnI-Gγ polymorphism, and clinical severity of β-thalassemia in northern Thailand. Material and Method: Thirty-two β-thalassemia major and 28 β-thalassemia intermedia attending the Thalassemia Clinic at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand were recruited. The β-globin gene mutations and SEA-α thalassemia 1 were determined by MS-PCR and Gap-PCR, respectively. The XmnI-Gγ polymorphism was identified by RFLP analysis. Odds ratio was calculated to evaluate the associations of these three genetic factors and clinical symptoms. Results: Eight β-globin gene mutations (both βOand β+) were found. Twenty-nine point one percent of the patients had at least one XmnI-Gγ site (XmnI-Gγ: +) and 4.1% of the patients were heterozygote for the SEA-α thalassemia 1. The β-globin gene mutations showed maximal impact and the XmnI-Gγ polymorphism had minimal influence on clinical severity in this cohort. The SEA-α thalassemia 1 had the least effect on the clinical severity due to its low prevalence in these patients. Conclusion: Although these three genetic factors play roles in modifying clinical symptoms of β-thalassemia, the β-thalassemia mutations should be considered first, followed respectively by the XmnI-Gγ polymorphism and the SEA-α thalassemia 1, in management and prenatal diagnosis of β-thalassemia in northern Thailand.